Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1992
DOI: 10.1007/bf01715348
|View full text |Cite
|
Sign up to set email alerts
|

Presence of more than two rearranged immunoglobulin heavy-chain genes in adult precursor B-cell acute lymphoblastic leukemia

Abstract: We examined the configuration of the immunoglobulin genes in the leukemic blast cell DNA of 20 adults with precursor B-cell acute lymphoblastic leukemia (ALL), treated according to the BMFT protocol. Sixteen of 20 (80%) patients expressed HLA-DR antigens and lacked detectable T-cell antigens. Eleven of the 20 patients (55%) were positive for the CD10 antigen and therefore classified as common ALL. Six patients were classified by immunological phenotyping as null-ALL (30%). Three patients (15%) expressed both i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1994
1994
2002
2002

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Kitchingman et al 18 detected hyperdiploidy in 9/18 pediatric patients with oligoclonality, and 8 of them presented polysomy of chromosome 14. Forestier et al, 35 Moreira et al 36 and Schardt et al, 30 in studies on children and adults, respectively, found no alterations of chromosome 14. In the present study, the karyotype was analyzed in 7/15 cases with bi/oligoclonality, and changes in chromosome 14 were detected in 2 cases, one of them with polysomy and the other with structural alterations, i.e.…”
Section: Sample Preparation and Polymerase Chain Reactionmentioning
confidence: 92%
See 1 more Smart Citation
“…Kitchingman et al 18 detected hyperdiploidy in 9/18 pediatric patients with oligoclonality, and 8 of them presented polysomy of chromosome 14. Forestier et al, 35 Moreira et al 36 and Schardt et al, 30 in studies on children and adults, respectively, found no alterations of chromosome 14. In the present study, the karyotype was analyzed in 7/15 cases with bi/oligoclonality, and changes in chromosome 14 were detected in 2 cases, one of them with polysomy and the other with structural alterations, i.e.…”
Section: Sample Preparation and Polymerase Chain Reactionmentioning
confidence: 92%
“…33,38 The presence of bi/ oligoclonality or clonal evolution, although relatively frequent, is mostly associated with the same D-JH sequence, with events in the rearranged VH gene being more common (VH to VH, VH to D-JH). 30,33,37,38,41 Bi/oligoclonality in a rearranged IgH gene has been detected in 20 to 50% of B-lineage acute lymphoblastic leukemia cases in studies by Southern blot 17,18,[30][31][32] and in 10-40% of cases by polymerase chain reaction. 20,31,33,34 The explanation for the difference in oligoclonality findings may be due to the fact that incomplete D-J rearrangements can be detected by southern blot but not by polymerase chain reaction.…”
Section: Sample Preparation and Polymerase Chain Reactionmentioning
confidence: 99%